Global research trends on maternal exposure to methylmercury and offspring health outcomes - Nascimento, Priscila Cunha; Ferreira, Maria Karolina Martins; Bittencourt, Leonardo Oliveira; Martins-Júnior, Paulo Antônio; Lima, Rafael Rodrigues (Frontiers in Pharmacology, 2022)
This study aimed to analyze the landscape of maternal methylmercury exposure and its offspring consequences based on knowledge mapping of the 100 most-cited papers about this theme. A search was performed using the Web of Science, without any restriction of language or publication year. Data bibliometrics, such as the number of citations, citation density, corresponding author's country, year of publication, study design, and keywords, were extracted from each paper and analyzed. VOSviewer software was used to create graphical bibliometric maps. Of a total of 1,776 studies on this theme, the 100 most-cited papers rendered the number of citations ranged from 110 to 1,356 citations. The non-systematic reviews and cohort studies from Anglo-Saxon countries published in the first decade of the 2000s were the most frequent. Clarkson, Grandjean, and Myers were the authors with higher citation density. A total of 520 keywords represented the evolution of the theme, from classic episodes of MeHg intoxication, as well as main the health changes until the different forms of exposure and, in recent years, biomonitoring studies were highlighted. Our findings provide the global research trends highlighting the network of most influential authors and a better understanding of the evolution and future scenarios of this theme.